2017
DOI: 10.1186/s13049-017-0425-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of upper gastrointestinal bleeding in emergency departments, from bleeding symptoms to diagnosis: a prospective, multicenter, observational study

Abstract: BackgroundUpper gastrointestinal bleeding (UGB) is common in emergency departments (EDs) and can be caused by many eso-gastro-duodenal lesions. Most available epidemiological data and data on the management of UGB comes from specialized departments (intensive care units or gastroenterology departments), but little is known from the ED perspective.We aimed to determine the distribution of symptoms revealing UGB in EDs and the hemorrhagic lesions identified by endoscopy. We also describe the characteristics of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
6
25
5
Order By: Relevance
“…We observed that age above 40 years was an independent predictor of mortality. This has also been noted in prior studies both in HIC and LMIC [1,5,13,14].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…We observed that age above 40 years was an independent predictor of mortality. This has also been noted in prior studies both in HIC and LMIC [1,5,13,14].…”
Section: Discussionsupporting
confidence: 84%
“…within 24 h of ED presentation. Compared with studies from HIC, patients in our study were of younger age, with the median age being 42 years [1,13,14,22]. We observed that age above 40 years was an independent predictor of mortality.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations